Fiber-broadband-intenet and its regional impact: An empirical investigation - Gordon Klein (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2020)
I analyze a quasi-natural experiment of fiber broadband rollout in a rural German area. The analysis particularly investigates the impact on real estate values. I find that there are strong and significant effects of fiber broadband deployment. These indicate that there are relevant personal benefits from broadband deployment for customers. Therefore, the findings add to the literature of evaluation of broadband infrastructure investment.
Keywords: 330; Broadband Internet; Real Estate Values; Quasi-natural experiment; Treatment Evaluation